2018
DOI: 10.1101/503755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biophysical characterizations of the recognition of the AAUAAA polyadenylation signal

Abstract: Most eukaryotic messenger RNA precursors must undergo 3¢-end cleavage and polyadenylation for maturation. We and others recently reported the structure of the AAUAAA polyadenylation signal (PAS) in complex with the protein factors CPSF-30, WDR33 and CPSF-160, revealing the molecular mechanism for this recognition. Here we have characterized in detail the interactions between the PAS RNA and the protein factors using fluorescence polarization experiments. Our studies show that AAUAAA is recognized with ~1 nM af… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Second, by searching for the most enriched motifs, we found that AAUAAA and U/GU rich motifs were the most significant motifs for WDR33 and CstF64, respectively (Supplemental Figure 5B), consistent with previous reports (16,49). Third, by focusing on the density of the reads closing to the canonical cleavage/polyadenylation (C/P) site, we observed peaks approximately 20 nt upstream of the C/P site for WDR33 and 10 nt downstream of the C/P site for CstF64 (Supplemental Figure 5B), which agree well with the current in vitro model for PAS recognition by CPSF/CstF (16,44,46,54,55). Two major observations were made from the iCLIP-seq analysis between the control and U1 AMO treated cells.…”
Section: U1 Amo Treatment Manipulates Cpsf/cstf Co-transcriptionallysupporting
confidence: 90%
“…Second, by searching for the most enriched motifs, we found that AAUAAA and U/GU rich motifs were the most significant motifs for WDR33 and CstF64, respectively (Supplemental Figure 5B), consistent with previous reports (16,49). Third, by focusing on the density of the reads closing to the canonical cleavage/polyadenylation (C/P) site, we observed peaks approximately 20 nt upstream of the C/P site for WDR33 and 10 nt downstream of the C/P site for CstF64 (Supplemental Figure 5B), which agree well with the current in vitro model for PAS recognition by CPSF/CstF (16,44,46,54,55). Two major observations were made from the iCLIP-seq analysis between the control and U1 AMO treated cells.…”
Section: U1 Amo Treatment Manipulates Cpsf/cstf Co-transcriptionallysupporting
confidence: 90%
“…Our 3'RACE results suggest that the first PAS encountered (ATTAAA) is preferentially used both before and after UV treatment (Figure 2D), whereas the downstream PAS (AATAAA) was used with less efficiency (and only after UV treatment). Although ATTAAA is the first encountered, it also has 5-6 times lower affinity for cleavage and polyadenylation specificity factor (CPSF) than AATAAA (87). However, it has also been shown that short (<10 bp) distances between PAS and GU-rich sequences might inhibit processing (88), explaining the lower usage of the second PAS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the poly(A) polymerase enzyme is a constitutive subunit of the yeast but not the human complex (Chan et al, 2014;Kaufmann et al, 2004). Human CPSF has a nanomolar affinity for PAS-containing RNA (Hamilton et al, 2019), while the interaction of CPF with RNA is orders of magnitude weaker (Hill et al 2019). In addition, human CStF and CFIIm are separate complexes, whereas in yeast, they form a constitutive complex called CF IA (Gordon et al, 2011;Schäfer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%